Um estudo sobre o uso do GeoGebra na aprendizagem de geometria analítica no ensino médio - Silva, Girleide Maria da (Universidade Federal de São Carlos, 2016)
This study investigated, in a quantitative-qualitative approach of a descriptive nature, the influence of Mathematics teaching combined with technological resources in the learning of some contents of Analytical Geometry. The aim of this study was to analyze the extent to which the software GeoGebra contributed to the learning of the content of point and line. Two groups of the daytime period of the 3rd grade of high school participated in the study of a public school in a city of São Paulo. Both classes were submitted to a Sequence of Activities that considered the different Registers of Semiotic Representation, according to Raymond Duval's Theory. The first group (T1), worked with activities in instructional and constructional approaches using GeoGebra, while the other (T2) worked the activities using pencil and paper. The data were obtained from a questionnaire about the participants' profile, a Pre-Test, Intermediate Evaluation and a Post-Test. Group 1 started the sequence with 0.15 points in relation to the average of the participants of Class 2, and ended with 0.71 points, that is, very close. We consider that for the two classes, the concepts were learned, since the averages in the post-test were 7.90 and 7.19, respectively. It was verified that in the questions that approached the abilities of visualization (locate, identify) and construction (trace, represent), Group 1 presented higher averages than the participants of Group 2, however in the questions that required calculation ability, Group 2 obtained better averages . In this way, we consider that GeoGebra contributed to the learning of point and straight contents, favoring the representation of mathematical objects in different registers. However, we believe that it should be associated with other methodologies that account for the students' comprehension and appropriation of calculation ability, which only the use of the software did not contribute to develop.
A study of the use of GeoGebra in analytical geometry learning in high school
Keywords: Educação matemática; Aprendizagem; Registros de representação semiótica; GeoGebra; Mathematics education; Learning; Semiotics representation registers; CIENCIAS HUMANAS::EDUCACAO